Sleep disturbances and behavioral symptoms in pediatric Sotos syndrome - Frattale, Ilaria; Sarnataro, Rachele; Siracusano, Martina; Riccioni, Assia; Galasso, Cinzia; Valeriani, Massimiliano; Conteduca, Giuseppina; Coviello, Domenico; Mazzone, Luigi; Moavero, Romina (Frontiers in Neurology, 2024)
Background Sotos syndrome (SoS) is a rare overgrowth genetic disease caused by intragenic mutations or microdeletions of the NSD1 gene located on chromosome 5q35. SoS population might present cognitive impairment and a spectrum of behavioral characteristics, with a worse profile in patients with microdeletion. Although patients with SoS are known to have impaired sleep habits, very little data are available. The present study aimed to assess the prevalence of sleep disorders (SDs) in a pediatric cohort of patients with SoS and their correlation with neuropsychiatric profiles. Methods We included patients with a SoS diagnosis and age < 18 years; all patients underwent a comprehensive neuropsychological assessment, including evaluation of cognition, adaptive functions through the Adaptive Behavior Assessment System-Second Edition (ABAS-II), and behavioral problems using the Achenbach Child Behavior Checklist (CBCL) and Conners’ Parent Rating Scale-Revised (CPRS-R:L) questionnaire. To investigate the presence of SD parents, the Sleep Disturbance Scale for Children (SDSC) was completed. Results Thirty-eight patients (M 61%, F 39%, mean age 11.1 ± 4.65 years) were included in the study. Although only two had a prior SD diagnosis, 71.1% (N = 27) exhibited pathological scores on SDSC. No statistically significant associations were found between positive SDSC results and genetic microdeletion, intellectual disability (ID), or other medical conditions/treatments. However, a positive correlation emerged between SDSC scores and Conners’ Global Index (p = 0.048) and Restless/Impulsive (p = 0.01) scores, CBCL externalizing (p = 0.02), internalizing (p = 0.01), and total scores (p = 0.05). Conversely, a negative linear relationship was observed between the SDSC score and the ABAS GAC and ABAS CAD scores (p = 0.025). Conclusion We detected an SD in 71.1% of our sample, with a positive relation between SD and internalizing and externalizing symptom levels, especially hyperactivity and impulsivity. Our study demonstrated a high prevalence of SD in pediatric patients with SoS, highlighting that all patients should be screened for this problem, which has a great impact on the quality of life of patients and their families.